Theory and practice of harmonization of rules on regional and multilateral bases : its relevance for World Trade Organization work on trade facilitation - Rege, Vinod (2002)
Examines how far, it would be possible to adopt binding rules which countries must apply to the movement and clearance of goods through customs.